Balancing Pay and Life: How Compensation and Work-Life Balance Drive Employee Performance through Job Satisfaction - Agung Sasmito Utomo; Mirwan Surya Perdhana; Khoiriyah Sari Pertiwi; Martinus Hendra Dewantara (Yayasan Darussalam Bengkulu, 2026)
Background: Employee performance is essential for organizational success and can be influenced by compensation, work-life balance, and job satisfaction. Understanding the relationships among these factors is important for improving employee productivity and organizational outcomes. Method: This study involved 149 employees of CV. X as respondents. Data were collected using a Likert-scale questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS), including validity, reliability, and hypothesis testing. Results: The findings show that compensation, work-life balance, and job satisfaction have positive and significant effects on employee performance. In addition, job satisfaction significantly mediates the effects of compensation and work-life balance on employee performance. Conclusion: Compensation and work-life balance contribute to improved employee performance both directly and indirectly through job satisfaction. Enhancing employee satisfaction through fair compensation and a balanced work environment can help organizations achieve better performance outcomes.